The influence of social capital, human capital, and natural capital on economic growth and community welfare - M Amin (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This study aims to determine the effect of social capital, human capital, and natural capital on economic growth and community welfare. The research method used is quantitative method. Data collection techniques are done by means of literature study and documentation. The results state that social capital has a significant effect on economic development and community welfare. Then the results of this study can provide answers regarding the phenomenon of the level of community welfare in West Nusa Tenggara Province which is currently still below the national average. Based on the research results, it is undeniable that to improve the welfare of the people in West Nusa Tenggara, a social capital-based economic growth management policy is needed. This should be done because economic growth is a good intervention variable for social capital. In addition, it is also necessary to pay attention to local governments so that regional financial management is based on the economic growth needed for the welfare of the people in West Nusa Tenggara. ]